Level of radicular stress in upper premolars and pressure exerted in adjacent tissues: a 3D mechanical model - Edison Guamaní Cayo; Ángel Morales Carrasco; Alex Morales Carrasco; Juan Viteri Moya; Ruth Vaca; Jonnathan Ochoa Guazhco; Paola Peralta Idrovo; Cristóbal Espinoza Diaz; Alicia de los Ángeles Morocho Zambrano; Zoila del Cisne Espinoza Diaz (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2023)
Objective: To compare the level of radicular stress and pressure exerted on adjacent tissues in 1.4 upper premolars with effect and without effect, vertical and axial compression splint in prefabricated posts, fiberglass and titanium vs cast noble metal (Au) and nickel chromium (NiCr) cast metal studs, cemented with self-adhesive self-conditioning resinous cement using the finite element technique. Materials and Methods: An experimental and comparative study was carried out with 8 simulated 3D models of 1.4 upper premolars. The FEMAP 11.1.2 software was used to model the mechanical design in 3D. Results: The radicular stress level is higher in the prefabricated cast Au and NiCr posts both at 360 and 180º compared to the fiberglass and titanium ones, the most representative average being in the NiCr at 360º with 104.23 Mpa and the lowest in Titanium 180º with 83.79 Mpa. The pressure exerted on adjacent tissues, in the premolars, has a higher level in prefabricated posts based on fiberglass and titanium at 180º compared to those made of noble metal and nickel-chromium, the most representative being that of smooth fiberglass at 180º with 1.43 and the lowest is the 360º NiCr with 1.30. Conclusion: The radicular stress level is higher in pre-cast Au and NiCr posts both at 360 and 180º compared to fiberglass and titanium posts, and the level of pressure exerted on adjacent tissues in the premolars has a higher level in prefabricated fiberglass and titanium bolts, both at 180º, compared to Au and NiCr.